Efficacy of cognitive behavioral therapy in reducing psychiatric symptoms in patients with implantable cardioverter defibrillator: an integrative review - Maia,A.C.C.O. (2014)
This article is a systematic review of the available literature on the benefits that cognitive behavioral therapy (CBT) offers patients with implanted cardioverter defibrillators (ICDs) and confirms its effectiveness. After receiving the device, some patients fear that it will malfunction, or they remain in a constant state of tension due to sudden electrical discharges and develop symptoms of anxiety and depression. A search with the key words “anxiety”, “depression”, “implantable cardioverter”, “cognitive behavioral therapy” and “psychotherapy” was carried out. The search was conducted in early January 2013. Sources for the search were ISI Web of Knowledge, PubMed, and PsycINFO. A total of 224 articles were retrieved: 155 from PubMed, 69 from ISI Web of Knowledge. Of these, 16 were written in a foreign language and 47 were duplicates, leaving 161 references for analysis of the abstracts. A total of 19 articles were eliminated after analysis of the abstracts, 13 were eliminated after full-text reading, and 11 articles were selected for the review. The collection of articles for literature review covered studies conducted over a period of 13 years (1998-2011), and, according to methodological design, there were 1 cross-sectional study, 1 prospective observational study, 2 clinical trials, 4 case-control studies, and 3 case studies. The criterion used for selection of the 11 articles was the effectiveness of the intervention of CBT to decrease anxiety and depression in patients with ICD, expressed as a ratio. The research indicated that CBT has been effective in the treatment of ICD patients with depressive and anxiety symptoms. Research also showed that young women represented a risk group, for which further study is needed. Because the number of references on this theme was small, further studies should be carried out.